Insulin degludec as an ultralong-acting basal insulin once a day: a systematic review - Wang, Fei (Dove Medical Press, 2012)
BACKGROUND: Insulin degludec (IDeg) is a neutral, ultralong-acting new generation basal insulin analog developed by NovoNordisk currently in Phase III clinical development. IDeg offers a duration of action of more than 42 hours in adults, much longer than current basal insulin formulations. OBJECTIVE: The aim of this review is to assess the efficacy and safety data of IDeg in the treatment of type 1 and type 2 diabetes mellitus. METHODS: Relevant English language articles from 2010 to 2012 were identified through MEDLINE, PubMed, EMBASE, Scopus, BIOSIS, and Google Scholar. Online conference proceedings of the 71st ADA Scientific Sessions and the 47th EASD Annual Meeting were reviewed. Studies were compared in terms of their study designs, primary and secondary efficacy parameters, and tolerability data. RESULTS: There are a total of nine published trials investigating the clinical efficacy and safety of IDeg in over 3000 subjects with type 1 and 2 diabetes. Only three trials were published in full. All were open-label, randomized multicenter trials with durations of 16 to 52 weeks. IDeg and coformulations of IDeg with insulin aspart (IAsp) were compared to insulin glargine (IGlar), detemir, and biphasic IAsp 30 (BIAsp 30). CONCLUSION: Based upon the available evidence, there appear to be no reported differences between IDeg and IGlar, detemir, or BIAsp 30 in the reduction of the primary efficacy end-points of HbA(1c) and mean fasting plasma glucose (FPG) concentrations. Only flexible dosing of IDeg provided a significant reduction in FPG compared to IGlar. IDeg demonstrated a significant reduction in nocturnal hypoglycemia in type 1 diabetes. In type 2 diabetes, IDeg reduced the incidence of hypoglycemia by 18% and 58% compared to IGlar and BIAsp 30, respectively.